Iron overload associated symptoms and laboratory changes in the Swiss Haemochromatosis Cohort – when a clinician should become attentive - Sebastian Kölmel; Albina Nowak; Pierre-Alexandre Krayenbuehl (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY